The Influence of Brand Image and Brand Trust on The Decision to Study in the Tax Accounting Study Program (Case Study at Politeknik Unggul LP3M) - Amelia, Ratih; Tambunan, Debora; Albert (Journal of Finance Integration and Business Independence, 2024)
This study examines the impact of brand image and brand trust on students' selection of Politeknik Unggul LP3M as their higher education institution. In the intensifying rivalry within the education sector, comprehending the determinants that affect prospective students' decisions is crucial. Brand image reflects public opinion of an institution, whereas brand trust signifies confidence in the institution's quality and dedication. This research utilized a quantitative methodology, gathering data using a questionnaire survey. The study's population consisted of all new students at Politeknik Unggul LP3M, from which a purposive sampling method was employed to pick a sample of 150 respondents. We employed regression analysis to assess the influence of independent variables on the decision-making process. The findings indicated that brand image and brand trust substantially affected students' choices. The managerial implications of these findings indicate that the administration of Politeknik Unggul LP3M must enhance its brand image by advocating for academic excellence, contemporary facilities, and community engagement. Moreover, maintaining uniformity in service and clarity in information helps enhance brand trust. We anticipate that this strategy will enhance the institution's competitiveness and attract additional students. The study's shortcomings encompass restricting the sample to new Politeknik Unggul LP3M students, potentially failing to fully represent the broader population of prospective students. We recommend broadening the sample size and incorporating more pertinent variables in subsequent study